Improving buildings refurbishment through operative conditions evaluation - Silva, Sandra Monteiro (2012)
As EU existing buildings stock account for 40% of the total energy consumption, it is important to take measures to reduce these needs and, consequently, reduce the EU external energy dependency as well as reducing the greenhouse gas emissions, in accordance with what is prescribed in the EU Directive 2002/91/EU on Energy Efficiency in Buildings (EPBD) and reinforced with the "EPBD-recast". The implementation of energy efficiency measures in the existing building stock is necessary to meet the 2020 targets. Thus, energy refurbishment of existing buildings is essential to achieve these goals. However, during the buildings refurbishment, energy issues should not be the only concerns since the indoor air quality is also as important. When planning a building refurbishment it is then necessary to take into account the energy efficiency exigencies and also the indoor air quality. To do so, the main problems of the existing buildings should be identified, in order to do the right choices regarding the refurbishment project. This work presents a study carried out in a large office building to identify the main pathologies, related to the energy efficiency and also to the indoor air quality. The study encompasses an “in-situ” evaluation of the operating conditions, indoor air quality and air change rate. The main objective of this study was to support the development of a refurbishment project of the building that can optimize the energy efficiency, but also the relevant parameters to the Indoor Air Quality. The results showed that the building has a poor envelope thermal resistance, inadequate shading systems and also several problems regarding high concentration of some pollutants like CO2 or VOC.